2024
DOI: 10.60083/jidt.v6i1.465
|View full text |Cite
|
Sign up to set email alerts
|

Application of The User Centered Design Method To Evaluate The Relationship Between User Experience, User Interface and Customer Satisfaction on Banking Mobile Application

Frans Sudirjo,
Dominica Maria Ratna Tungga Dewa,
Lucky Indra Kesuma
et al.

Abstract: The aim of this research is to evaluate user satisfaction through UI/UX design in mobile banking and find out what kind of UI/UX appearance users want using the user-centered design method. This research uses a qualitative approach. In addition to the qualitative approach, this research also incorporates a quantitative approach. Data collection in this research used usability testing, interviews, and questionnaires. We calculated the data obtained from the questionnaire statistically using Microsoft Excel. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
1
Order By: Relevance
“…By understanding customer satisfaction through an EUCS lens, service providers can gain deep insight into which areas need improvement. Furthermore, the results of this research can offer concrete recommendations to enhance service quality, improve user experience, and foster customer trust in the rapidly evolving digital service landscape [11]. The findings of a number of earlier research that examined people's interest in utilizing digital wallet applications have shown to be extremely insightful.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…By understanding customer satisfaction through an EUCS lens, service providers can gain deep insight into which areas need improvement. Furthermore, the results of this research can offer concrete recommendations to enhance service quality, improve user experience, and foster customer trust in the rapidly evolving digital service landscape [11]. The findings of a number of earlier research that examined people's interest in utilizing digital wallet applications have shown to be extremely insightful.…”
Section: Introductionmentioning
confidence: 90%
“…It seems that there are certain factors that significantly affect people's interest in using digital wallet applications, based on the findings of study conducted on respondents who are users of these apps. Initially, a number of criteria were found to have an impact on people's interest in utilizing digital wallet applications [11]. These factors included knowledge, service features, perceived convenience, perceived benefits, pricing, trust, and sales incentives.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the fintech industry has also had an impact on the establishment of businesses in the digital finance space. Digital wallets and electronic money are two of these technologically advanced financial instruments [3]. The advent of electronic money and e-wallets will allow people to conduct transactions in a cashless world [4].…”
Section: Introductionmentioning
confidence: 99%
“…The assessor will provide a figure illustrating the difference between better and worse performance. The oldest and most popular approach is the rating scale method, in which supervisors or superiors evaluate employees based on traits including initiative, reliability, maturity, and contribution to work goals [20]. Expert evaluations are based on their judgments, and frequently, the standards have little to do with the task output.…”
Section: Introductionmentioning
confidence: 99%